Atividade dos músculos sóleo, gastrocnêmio cabeça lateral e cabeça medial durante exercícios realizados no smith, leg press e gêmeos sentado em três diferentes posições dos pés - Azevedo, Jônatas Bezerra de (2018)
The plantar flexion as training of the gastrocnemius lateral head, medial head and soleus muscles (GL, GM and SOL) can be performed on different types of equipment and foot positions. Dentros of the academies in an impersonal way students and coaches use the feet in standing position inwards, standing out and standing forward in order to perform exercises for the triceps sural. The objective of this study was to verify the activity of GL, GM and SOL muscles during exercises performed on different equipment and foot positions. The sample consisted of 15 healthy men (Age 26.8 ± 5, Weight 77.6 ± 10.8, Height 172.6 ± 6), physically active. Surface electromyography of the GL, GM and SUN muscles was collected during the plantar flexion movement considering 5 repetitions with the same load obtained in the test of 10 maximum repetitions in the Leg Press, Smith and Sit Twins equipment. For each apparatus, 3 collections were performed with 5 replicates, 5 minutes between collections and 5 minutes between the equipment. The two-way analysis of variance showed no significant difference in the activity of the three muscles in relation to the position of the feet (F = 0.21, P = 0.97, p2p2 = 0.005) (F = 0.02, P = 1.00, p2p2 = 0.001). However, the type of equipment used for the exercise of these muscles had a significant influence (F = 11.55, P = <0.001; p2p2 = 0.20). The exercises of plantar flexion performed with 5 repetitions in Smith provide a significant increase in GL and GM muscle activity in relation to the exercises performed in the Leg Press and Sitting Twin equipment. It was not found in soleus muscle activity. The activity of these muscles is not influenced by the changes in the position of the feet during the exercises performed in these three equipments.